Conversations on Electric and Magnetic Fields in the Cosmos. - Parker, Eugene N. (Princeton series in astrophysics., 2013)
Today's standard textbooks treat the theoretical structure of electric and magnetic fields, but their emphasis is on electromagnetic radiation and static-electric and magnetic fields. In this book, Eugene Parker provides advanced graduate students and researchers with a much-needed complement to existing texts, one that discusses the dynamic electromagnetism of the cosmos--that is, the vast magnetic fields that are carried bodily in the swirling ionized gases of stars and galaxies and throughout intergalactic space. Parker is arguably the world's leading authority on solar wind and the effe.